Morphological considerations pertaining to recognition of atrial isomerism. Consequences for sequential chamber localisation. Issue 6 (December 1980) - Macartney, F J; Zuberbuhler, J R; Anderson, R H
Abstract : The atrial morphology and venous connections were assessed "blind" in 51 necropsy specimens from patients with visceral heterotaxy. This was compared with bronchial morphology as established by dissection. Six specimens were found to have both atria and bronchi in situs solitus or inversus, and were rejected. In the remainder, atrial isomerism was diagnosed, though this required minor revision of the atrial assessment in two patients. Thirty-four patients had isomeric right atria and bronchi, while 11 had isomeric left atria and bronchi. In seven cases, splenic status was unknown, but in seven of the remaining 38 (18.4%) atrial isomerism was not associated with either asplenia or polysplenia. Nevertheless, right isomerism was strongly associated with total anomalous pulmonary venous drainage (as is asplenia) and left isomerism was likewise associated with interruption of the inferior vena cava (as is polysplenia). Bilateral superior venae cavae and hepatic veins, and absence of the coronary sinus, were frequent in both forms of isomerism (as they are in asplenia and polysplenia). These findings suggest that atrial situs can be defined as solitus inversus, right isomerism, and left isomerism. This determination of atrial situs is quite independent of any other abnormalities of visceral situs. The high incidence of anomalies of both venous return and common atrium resulted in presumed complete mixing of blood at atrial level in all but one patient (97.8%), making the haemodynamic connection between atria and ventricles almost always ambiguous. To describe this anatomical connection as ambiguous when there are two ventricles present is therefore no more than recognition of anatomical and haemodynamic reality.